Measures developed by the nurses for the adolescents in the family health program in Maringá/Paraná - Higarashi, Ieda Harumi; Roecker, Simone; Baratieri, Tatiane; Marcon, Sonia Silva (Rev Rene, 2011)
This study aimed at characterizing the measures of disease prevention, encouragement and recovery of the adolescents’ health accomplished by the nurses of the Family Health Program (FHP) in the municipal district of Maringá/PR. As participants of the research, there were, eight nurses, representing the five micro-regions that compose the municipal district. Data was collected through semi-structured interviews, in the month of May 2009, having as methodological referential the qualitative approach for content analysis. The results of the study showed that nurses develop actions for disease prevention and health encouragement, through individual orientations, lectures in schools and adolescent group, especially related to sexuality and drugs. It was also noticed, a gap of assistance attributed to the low demand of adolescents who spontaneously seek the service of health, the absence of systematized actions directed to this clientele and the lack of formative resources which come to support a more effective action of the health professionals in this area.